If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x = 7x + -20 Reorder the terms: 11x = -20 + 7x Solving 11x = -20 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 11x + -7x = -20 + 7x + -7x Combine like terms: 11x + -7x = 4x 4x = -20 + 7x + -7x Combine like terms: 7x + -7x = 0 4x = -20 + 0 4x = -20 Divide each side by '4'. x = -5 Simplifying x = -5
| 23-x=22 | | (2x+1/3)^2=0 | | 55=(3x-1)(5) | | 2(2k-5)-k=4-(3k+7) | | 49-x=14 | | -16-8= | | 26X+12=5(5X+7) | | 10+2-x/3=7 | | 32n+12-20=12n+16+1 | | 9d/12-d/12 | | v*7=8 | | 70=(x+4)(7) | | m*4=-13 | | (-8x-4y/2x)+(6x-11y/2x) | | 6x+10=-6+58 | | 2(y+5)=3(y-15)+20 | | 4=(.300+x)(.200+x) | | 1/4(x-12) | | 15x+10y=90 | | -1/2(8+6) | | 15x+10x=90 | | 7(8-3)= | | k=k*11 | | -2z-4(10-4z)=-2 | | 36x+11=5x^2 | | -4(x-4)-2x=8-6(x+3) | | 3a-a+1=5 | | 5=2(3-8q)-2q | | 3[2+6(8-7)]= | | -1-2/7v2 | | -7=-(1-3a)-5a | | 4x+2=6x+9 |